The personality types of key catalytic individuals shape colonies' collective behaviour and success - Pruitt, Jonathan N. (Anim Behav, 2014)
Behavioural ecologists often note that one or a few group members appear to shape the collective behaviour of social groups differentially. Our understanding of these keystone individuals is largely taken from meticulous field observations and semi-scientific anecdotes. In this study we experimentally test whether the behavioural tendencies of putative keystone individuals shift the collective behaviour of colonies using the social spider Stegodyphus dumicola. Prior studies on Stegodyphus demonstrated that the single best predictor of colonies' collective behaviour is the behaviour of colonies' boldest individual. Here, we probe the causal relationship between the traits of extremely bold individuals and colonies' collective behaviour by experimentally creating colonies of identical size and personality composition in the laboratory and then adding a single individual of varying boldness (the putative keystone individual). Experimentally adding just one extremely bold individual increased the foraging aggressiveness of entire colonies and altered the total mass gained by fellow group members, relative to the addition of a less bold individual. Additionally, our data suggest that bold individuals are capable of such influence because they catalyse variation in the behavioural tendencies of fellow group members.